Developing an automated methodology for orthodontic correction of a CAD dental model - Yeo, Jesslyn (Nanyang Technological University, 2021)
Orthodontics treatment using the aid of 3D printing technology has increased significantly in recent years. One popular treatment for mild cases of misalignment is the use of a clear dental aligner. Attributes such as aesthetically pleasing, invisible and comfortable have made these clear dental aligner the preferred choice of treatment over traditional metal braces. The traditional treatment process for the fabrication of a dental aligner is labour-intensive and requires frequent recurring visits for check-up throughout the duration of the treatment. Hence, this FYP explores the possibility of automating the orthodontics correction via CAD models (using software) so as to increase the efficiency, planning and overall quality of the treatment process. The objective of this FYP is to set up a sequence of systematic steps to correct mild cases of malocclusion in CAD models with the use of MATLAB. This is to produce a series of dental models with progressive correction of malocclusion for easy fabrication of clear dental aligners. Simulation of the step correction is performed using ANSYS Spaceclaim and MATLAB. This report outlines the list of steps established by the author using finite element shape functions and 3D mesh morphing technique to generate the step correction algorithm as well as handling 3D dental models in STL file format and 3D modelling of the dental models using ANSYS Spaceclaim. This report also demonstrates the fabrication of the dental aligners after the step correction procedures and discusses the limitations of the methodology.